Mesenchymal stem cells modulate differentiation of myeloid progenitor cells during inflammation - Amouzegar, Afsaneh (Stem Cells, 2017)
Mesenchymal stem cells (MSCs) possess distinct immunomodulatory properties and have tremendous potential for use in therapeutic applications in various inflammatory diseases. MSCs have been shown to regulate pathogenic functions of mature myeloid inflammatory cells, such as macrophages and neutrophils. Intriguingly, the capacity of MSCs to modulate differentiation of myeloid progenitors to mature inflammatory cells remains unknown to date. Here, we report the novel finding that MSCs inhibit the expression of differentiation markers on myeloid progenitors under inflammatory conditions. We demonstrate that the inhibitory effect of MSCs is dependent on direct cell-cell contact and that this intercellular contact is mediated through interaction of CD200 expressed by MSCs and CD200R1 expressed by myeloid progenitors. Further, using an injury model of sterile inflammation, we show that MSCs promote myeloid progenitor frequencies and suppress infiltration of inflammatory cells in the inflamed tissue. We also find that downregulation of CD200 in MSCs correlates with abrogation of their immunoregulatory function. Collectively, our study provides unequivocal evidence that MSCs inhibit differentiation of myeloid progenitors in the inflammatory environment via CD200-CD200R1 interaction.